Energy-Efficient Programming Languages for Mobile Applications - Mahadevappa, Shashikala; Figueira, Silvia (2021 IEEE Global Humanitarian Technology Conference (GHTC), 2021)
Mobile devices, particularly cellular phones, play a significant part in people's lives everywhere. However, people in remote rural areas lack access to power and face power outages, which make it hard for them to charge their devices. Therefore, applications running on these devices must be as energy efficient as possible. In this paper, we analyze how different programming languages affect the energy consumption of applications in mobile devices. Considering that watching videos is one of the most commonly performed and power-hungry activities on mobile devices, we compare the implementation of video operations using three different programming languages: Java, Kotlin, and React Native. We show that the choice of programming language may make an application more energy efficient. Besides, the device model, Android version, and API used all affect battery usage. We also show that not all programming languages yield battery savings when compromising video quality. We believe these results will provide an important insight for application developers on the factors to consider when developing energy-efficient applications for mobile devices.